Direct Growth of Vertically Aligned Carbon Nanotubes onto Transparent Conductive Oxide Glass for Enhanced Charge Extraction in Perovskite Solar Cells. Issue 21 (9th September 2020) - Ferguson, Victoria; Li, Bowei; Tas, Mehmet O.; Webb, Thomas; Sajjad, Muhammad T.; Thomson, Stuart A. J.; Wu, Zhiheng; Shen, Yonglong; Shao, Guosheng; Anguita, José V.; Silva, S. Ravi P.; Zhang, Wei
Abstract: Vertically aligned carbon nanotubes (VACNTs) present an exciting avenue for nanoelectronics due to their predetermined orientation and exceptional transport capabilities along the tube length, with the potential to be employed in a variety of optoelectronic applications. However, growth of VACNTs using conventional chemical vapor deposition (CVD) methods requires elevated temperatures (>720 °C) and therefore, the suitability of commonly used transparent conductive oxide (TCO) glasses, such as fluorine‐doped tin oxide (FTO) and indium‐tin oxide (ITO), as the substrates for nanotube growth are limited by their temperature‐sensitive nature. Here, the successful growth of multi‐walled VACNTs directly onto commonly used TCO glasses, FTO and ITO, using the photo‐thermal chemical vapor deposition (PTCVD) growth method is reported. The benefit of reflection, within the infrared region, of the TCO substrate and the effect of surface roughness on the growth of VACNTs is investigated. The application of VACNTs on ITO in inverted planar perovskite solar cells is investigated, which shows superior charge transfer, larger grain sizes in the perovskite film, and a champion device efficiency approaching 16%. Abstract : Vertically aligned carbon nanotubes are grown directly onto temperature‐sensitive transparent conductive oxide glass; the morphology, quality and electrical properties are analyzed and used to fabricate optimized patterned carbon nanotube forest films which are used in perovskite solar cells to improve charge extraction resulting in a champion efficiency approaching 16%.